Patients’ perception and experience of using guided self-help for depression and anxiety in a primary care setting - Goodman, Lisa (2010)
Objectives. There is a developing body of evidence that guided self-help can be effective in alleviating distress experienced from symptoms of depression and anxiety. However evidence is not consistently positive and clarification is required about how it achieves its effects. Furthermore, previous research into guided self-help has not investigated patients with milder depression or anxiety. Exploration of the therapy process in guided self-help has crucial importance in developing further understanding about its qualities and how it is experienced. This study aimed to explore the ways in which people experience guided self-help for depression or anxiety within primary care.